Factors Related to Vaccine Hesitancy in Anti-vaccine Group on Facebook - Aisyah Nur Izzati; Budi Utomo; Retno Indarwati (Jurnal Ners, 2020)
Introduction: The current controversial issue regarding the anti-vaccine movement is the biggest challenge in implementing immunization in Indonesia because it influences the stagnation in the coverage of complete basic immunization. The World Health Organization (WHO) also states that the anti-vaccine group is one of the ten major threats to global health in 2019 since this phenomenon can cause rare diseases to become epidemic. This study aims at factors related to vaccine hesitancy in the anti-vaccine group on Facebook.Methods: This study used a descriptive correlational method with a quantitative approach. The sample in this study was 150 mothers who were members of the anti-vaccine group on Facebook social media, selected using a purposive sampling technique.Results: Demographic characteristics include religion, ethnicity, education, and income. Perceived susceptibility and perceived severity were assessed using Hwang’s Health Belief Model questionnaire, while vaccine hesitancy was assessed using Saphiro’s Vaccine Hesitancy Scale questionnaire, then analyzed using Spearman Rho (α<0.05). The results of this study showed that there was a correlation between perceived susceptibility and perceived severity of vaccine hesitancy (p=0.000), while demographic characteristics were not related to vaccine hesitancy.Conclusion: Certain religions and ethnicities which have caused concern have proven unrelated to parent’s hesitance in immunization, as well as the level of education and income. The vulnerability and severity of a disease emerged as most parents’ overriding concern when making decisions about vaccine